2022
DOI: 10.1371/journal.pone.0263277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medical management in Coronary Type 2 Diabetic patients with previous percutaneous coronary intervention in Spain: A retrospective analysis of electronic health records using Natural Language Processing

Abstract: Introduction and objectives Patients with type 2 diabetes (T2D) and stable coronary artery disease (CAD) previously revascularized with percutaneous coronary intervention (PCI) are at high risk of recurrent ischemic events. We aimed to provide real-world insights into the clinical characteristics and management of this clinical population, excluding patients with a history of myocardial infarction (MI) or stroke, using Natural Language Processing (NLP) technology. Methods This is a multicenter, retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In line with previous publications, we found that insulin treatment was associated with MACE occurrence [ 10 , 33 ]. Although randomized trials have shown that insulin reduces adverse cardiovascular events [ 27 ], in these patients insulin tends to be prescribed in more advanced phases of the disease, which could explain our findings.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with previous publications, we found that insulin treatment was associated with MACE occurrence [ 10 , 33 ]. Although randomized trials have shown that insulin reduces adverse cardiovascular events [ 27 ], in these patients insulin tends to be prescribed in more advanced phases of the disease, which could explain our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that: (1) T2DM patients who develop CAD are predominantly male with arterial hypertension, hyperlipidemia and obesity as the most prevalent comorbidities; (2) these patients present an increasing probability of developing MACE during the study follow-up; and (3) in this population the risk factors associated with the development of MACE are related with cardiovascular diseases (multivessel or single vessel disease, PCI, transient ischemic attack, heart failure) and T2DM severity (insulin treatment), whilst lipid lowering control strategies (treatment with statins) seems to be a protective factor. The described methodology has been recently used in the same cohort of patients to describe medical management in coronary T2DM patients with previous percutaneous coronary intervention in Spain, where the EHRead ® ability to correctly identify patients’ records containing key variables associated with the study disease is shown [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations